From Long-Run Utopia to Technical Expertise: Solow's Growth Model as a Multipurpose Design - Verena Halsmayer (Duke University, Center for the History of Political Economy (CHOPE), 2014)
Combining concrete policy-oriented modeling strategies of World War II with what was received as traditional neoclassical theory, in 1956 Robert Solow constructed a simple, clean, and smooth-functioning "design" model that served many different purposes. As a working object it enabled experimentation with long-run equilibrium growth. As an instrument of measurement it was applied to time series data. As a prototype it was supposed to feed into larger-scale econometric models that were, in turn, thought of as technologies for policy advice. Used as a teaching device, Solow's design became a medium of "spreading the technique," and one of the symbols for neoclassical macroeconomics that soon became associated with MIT.
Keywords: B22; B23; B31; B40; O4; Z1; 330; model; modeling; Robert Solow; growth theory; growth; neoclassical growth model; linear programming; dynamic programming; design model; Harvard Economic Research Project; Massachusetts Institute of Technology